Lexicons Per-tuak-an on Mambal Village Community of Badung Bali Regency in Ecolinguistic Perspective - I Nyoman Bawa Bagiada (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2019)
This research aims is to find out the interpersonal relations in the tuak lexicon and the dimension of social praxis that is owned by the tuak lexicon. The data of this research are oral data and written data as supporting data. The data collection method are observation and interviews with recording techniques and documentation techniques. The results of this research are the existence of interpersonal relations in the tuak lexicon based on naming, materials used and coloring whereas the dimensions of social praxis that form tuak are sociological, ideological and biological dimensions that arouse human ecological nature for conservation efforts. This encourages the government to preserve palm wine by introducing them to foreign tourists so that it can improve people's lives. The more familiar the palm wine among the community, it will increase the interaction between one community and another so that it will indirectly preserve the palm wine lexicon itself.